2004
DOI: 10.1128/iai.72.3.1637-1644.2004
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Endogenous Leukotrienes Exacerbates Pulmonary Histoplasmosis

Abstract: Leukotrienes are classical mediators of inflammatory response. New aspects of leukotriene function have recently been described. We examine here the previously unreported role that leukotrienes play in the regulation of cytokines in a murine model of histoplasmosis. We demonstrate that administration of MK 886, a leukotriene synthesis inhibitor, caused Histoplasma capsulatum-infected mice to die by the day 15 of infection, whereas the correlating death rate in untreated infected mice was 0%. Treating infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
0
29

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(169 citation statements)
references
References 36 publications
8
132
0
29
Order By: Relevance
“…Whether LTB 4 could be a useful immunostimulant for the treatment of infectious diseases remains to be investigated in clinical trials; numerous animal studies have already reported a beneficial effect of this eicosanoid models of infection (57)(58)(59)(60)(61)(62)(63)(64). LTB 4 administration to humans has been documented (29,65,66), with pharmacodynamic effects (␣-defensin and MIP-1␤ release (29) and PMN count variations (our unpublished data)) similar to what is reported in this study in monkeys without significant adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Whether LTB 4 could be a useful immunostimulant for the treatment of infectious diseases remains to be investigated in clinical trials; numerous animal studies have already reported a beneficial effect of this eicosanoid models of infection (57)(58)(59)(60)(61)(62)(63)(64). LTB 4 administration to humans has been documented (29,65,66), with pharmacodynamic effects (␣-defensin and MIP-1␤ release (29) and PMN count variations (our unpublished data)) similar to what is reported in this study in monkeys without significant adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…An important role for endogenous LTs in host defense was first demonstrated by Bailie et al (34), who reported that 5-LO-deficient mice exhibited impaired survival and pulmonary bacterial clearance in a model of K. pneumoniae pneumonia. Subsequent studies have documented a protective function of endogenous LTs in animal models including bacterial peritonitis (20), fungal pneumonia (35), and viral CNS infection (36). The effector functions involved in innate immune responses that are influenced by LTs include direct effects on leukocyte accumulation as well as their capacity for microbial phagocytosis and killing and indirect effects mediated by elaboration of other inflammatory molecules.…”
Section: Antimicrobial Effector Functions Of Ltsmentioning
confidence: 99%
“…Our results, together with those reported by Peres et al (6), suggest that LT can modulate soluble factors related to protection, such as IFN-γ and nitrite, and can stimulate the recruitment of leukocytes to the site of infection. In a similar manner, treatment of BALB/c mice with MK-886 increased their susceptibility to infection with H. capsulatum (8). On the other hand, Bafica et al (16) demonstrated that 5-lipoxygenase (5-LO -/-) knockout mice were more resistant to M. tuberculosis infection than wild-type mice.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, during a secondary immune response against infection by Histoplasma capsulatum, LT play a role by recruiting memory CD4+ and CD8+ cells to the lung (7). The activity of LT as powerful leukotropic and proinflammatory mediators involved in host defenses in a variety of infectious diseases (6,8,9), including mycobacterial infections (6), led us to suggest that LT might be involved in the protective immune response generated by heterologous prime-boost immunization with Bacille Calmette-Guérin (BCG) prime/DNA-HSP65 booster against M. tuberculosis infection.…”
Section: Tuberculosis (Tb) Is a Disease Caused By Infection Withmentioning
confidence: 99%
See 1 more Smart Citation